An ethnomathematics study on Rumah Kelantan Tiang 12 - Wan Bakar, Wan Bakar (Journal of Islamic, Social, Economics and Development, 2026)
This study investigated the ethnomathematical dimensions of the traditional rumah Kelantan Tiang 12, a distinctive symbol of Malay architectural heritage in Kelantan, a state on the east coast of Malaysia. Framed within the lens of ethnomathematics, the research examined how mathematical knowledge is woven into the design, construction and cultural meaning of the house. A qualitative methodology was adopted encompassing field observations, architectural measurements, photographic documentation and a review of relevant literature. The findings revealed a rich presence of mathematical concept: geometric forms in floor layouts and roof structures, proportional systems derived from traditional units of measurement and symmetrical arrangements that reflect balance and harmony. The twelve central pillars were found to embody both structural necessity and cultural symbolism, representing stability, identity and continuity of tradition. This study concluded that master builders applied mathematical reasoning intuitively, transmitted through generations of practices rather than formal instruction. By uncovering these embedded mathematical elements the research contributes to the preservation of Malay cultural knowledge while also demonstrating the potential of ethnomathematics to enrich mathematics education through culturally grounded learning experiences.